Molecular cloning and expression of hipA, a gene of Escherichia coli K-12 that affects frequency of persistence after inhibition of murein synthesis. - Moyed, H S (1986)
The hipA gene at 33.8 min on the Escherichia coli chromosome controls the frequency of persistence upon inhibition of murein synthesis; for strains bearing hipA+ the frequency is 10(-6), and for hipA- strains the frequency is 10(-2). hip+ has been cloned by selection for a kanamycin resistance determinant at 33.9 min. hipA+ is dominant over hipA- in both recA+ and recA- backgrounds. The smallest DNA insert which contains hipA+, as determined by the ability of the plasmids to complement hipA- strains, is 1,885 base pairs. Both orientations of hipA+ are obtained when the cloning site of vector is remote from strong promoters; both orientations complement hipA-, and both encode a unique peptide of 50,000 Mr. The probable direction of transcription has been deduced from the pattern of peptides encoded by plasmids from which either end of the insert and adjacent vector sequences have been deleted. This information and the recovery of only one orientation of hipA+ when the cloning site is close to a strong promoter suggest that a high level of expression of the gene is not tolerated by E. coli.